2020
DOI: 10.1016/j.xkme.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass Assessment by 1- and 2-Dimensional Echocardiographic Methods in Hemodialysis Patients: Changes in Left Ventricular Volume Using Echocardiography Before and After a Hemodialysis Session

Abstract: Rationale & Objective Left ventricular (LV) mass (LVM) is a predictor of cardiovascular morbidity and mortality and commonly calculated using 1-dimensional (1D) echocardiographic methods. These methods are vulnerable to small measurement errors and LVM may wrongly change according to changes in LV volume (LVV). Less commonly used 2-dimensional (2D) methods can accommodate to the changes in LVV and may be a better alternative among patients receiving hemodialysis (HD) with large fluid fluctuations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Recent studies questioned the accuracy of the DEV method in patients with concentric LV hypertrophy 7 , 9 , 13 . Both methods (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies questioned the accuracy of the DEV method in patients with concentric LV hypertrophy 7 , 9 , 13 . Both methods (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 , both the DEV and TEICH methods rely on the assumption that the LV is a prolate ellipsoid based on the cubic (CUBE) equation developed and refined by Dodge et al 11 , 12 . Indeed, alternative measurement methods with higher agreement and precision have been proposed for Echo 13 , 14 , but require multiple measurements or depend on image quality, such as in three-dimensional Echo. However, the TEICH method has not been systematically evaluated on a large cohort of patients for its feasibility and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…LV mass quantification by the linear method is prone to wrongly changes according to changes in LV volume. For example, the large fluid shift in hemodialysis patients, which causes significant differences in end-diastolic LV internal diameters, apparently affects LV mass calculations by linear methods, but not by the 2D echocardiographic area-length method [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been con rmed that increased LVM is closely related to poor prognosis of MHD patients, left ventricular hypertrophy (LVH) is often considered as a surrogate end point for all-cause and cardiovascular mortality outcomes. Paoletti et al followed up 123 MHD patients for 10 years, and found elevated LVMI is the strongest predictor of SCD [16][17] . This study once again proves patients with increased LVMI have higher 5-year mortality.…”
Section: Discussionmentioning
confidence: 99%